(untitled) (Journal of Technology and Operations Management, 2025)
The use of technology in various public sectors has an impact on the ease of carrying out operational activities, including in the food industry sector. Technology can be useful in various activities in the food industry, from the production process, distribution, to reaching consumers. It is hoped that the existence of technology will not only help in making the process better but can also improve and betterquality results. This research was conducted to determine the readiness of the food industry in Indonesia to accept the existence of technology itself. This research was carried out by distributing questionnaires to 32 respondents who were actors in the food industry. The results obtained are that currently food industry players know the existence and benefits of this technology for their business. Furthermore, using Sem-PLS analysis, the results obtained showed that the most influential variable was related to perceived ease of use. Therefore, a strategy is needed to encourage food industry players to want to use and understand this technology, so that later it can be used easily and beneficially for their business.